Involvement of stakeholders in the adoption and implementation of energy retrofits in hotel buildings. Issue 6 (18th May 2020) - Fasna, M.F.F.; Gunatilake, Sachie
Abstract : Purpose: Existing buildings encompass the largest segment of the built environment and, hence, have become a key target for energy retrofits (ER) to substantially reduce global energy usage. The success of ER projects is closely linked to the effective involvement of various stakeholders within the decision-making process. This paper aims to investigate different stakeholders and their involvement throughout the decision-making process of ER projects. Design/methodology/approach: Two successfully implemented ER projects in existing hotel buildings were selected as cases to gain novel insights into the key stakeholders to be involved along with their functions and roles in five different stages of the ER decision-making process. To collect required data, in total 11 semi-structured interviews were conducted with stakeholders involved in different stages of the decision-making process in the respective case studies. Data was analysed using code-based content analysis with the aid of NVivo computer software. Findings: Altogether, 18 stakeholders and 7 roles reflective of the nature of their involvement in the respective stages were established. Findings disclosed that the nature of the project, level of knowledge, expertise and commitment of internal staff, type of ownership of the facility and mode of financing have significant influence on involvement of different stakeholders in ER projects. Originality/value: The findings of this study are useful in enhancing the successful adoption and implementation of ER through timely and effective involvement and integration of stakeholders.